Antiferromagnetic domain structure in tetragonal CuMnAs films: A picturebook of domains, domain walls and everything in between - Reimers, Sonka (2022)
In antiferromagnetic (AF) materials, magnetic moments align in a regular pattern such that the moments cancel perfectly in each magnetic unit cell. Hence AF materials do not show a net magnetisation and are largely inert against magnetic fields. Thus, the hidden order of antiferromagnets has only been revealed in the last century. For spintronic applications, the use of antiferromagnets promises numerous advantages compared to conventional spintronics based primarily on ferromagnetic (FM) materials. Amongst the key materials for AF spintronics research are tetragonal, antiferromagnetic CuMnAs films, because in addition to being antiferromagnetically ordered at room-temperature, tetragonal CuMnAs is one of only two conductive AF materials, for which it has been shown that the AF order can be manipulated with electrical currents. This has raised hopes for antiferromagnetic memory devices where the AF order in CuMnAs is switched electrical between two different states.